Mechanical Ventilation in Neonates and Children A Pathophysiology-Based Management Approach - Sarnaik, Ashok P.; Venkataraman, Shekhar T.; Kuch, Bradley A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This textbook comprehensively covers mechanical ventilation in neonates and children integrating the latest knowledge and understanding of developmental biology, age-related and disease-specific physiologic differences in the practice of mechanical ventilation. The physiology associated with ventilation and lung mechanics are described. Guidance is provided on how to carry out a range of clinical assessments appropriately, including those for ventilation, mechanics and breathing control. Available pathophysiology-based management strategies for a range of situations including respiratory failure and ventilatory failure are also provided. Mechanical Ventilation in Neonates and Children: A Pathophysiology Based Management Approach broadly covers a range of topics associated with mechanical ventilation in children and neonates. It is a valuable resource for specific seminars or courses that concentrate on respiratory failure in children and for those preparing for board certification examinations for neonatal/perinatal medicine and pediatric critical care medicine. .
Mechanical Characteristics of the Lung and the Chest Wall -- Physiology of Inflation and Deflation -- Gas Exchange -- Clinical Examination and Assessment -- Monitoring -- Ventilators and Modes -- Mechanical Ventilation Strategies -- Mechanical Ventilation for Neonates -- Ventilator graphics -- Noninvasive Mechanical Ventilation -- Respiratory Care Equipment -- Chronic Ventilation and Home Care -- Case-based Analysis of Respiratory Failure.
Keywords: Critical care medicine; Pediatrics; Internal medicine; Intensive Care Medicine; Pediatrics; Internal Medicine; Internal Medicine; Respiration, Artificial -- methods; Ventilators, Mechanical; Respiratory Insufficiency -- physiopathology; Respiratory Insufficiency -- therapy; Infant, Newborn; Child